THE SIGNIFICANCE OF STATISTICS IN THE MACROECONOMIC DEVELOPMENT OF UZBEKISTAN - Gulomova Mashkhurakhon Rafiqjon qizi (Ecomind Press, 2025)
The article examines the role of statistical data in managing the macroeconomic development of Uzbekistan. It analyzes how modern official statistics serve as a basis for shaping state policy, assessing the effectiveness of reforms, and attracting investments. Special attention is paid to the transformation of the country's statistical system in the context of Uzbekistan's development strategy until 2030. Key challenges and directions for improving statistics to enhance the quality of macroeconomic analysis and forecasting are identified.
Keywords: Official statistics, macroeconomic development, Uzbekistan, system of indicators, economic growth, public administration, reforms, data, monitoring, SDGs (Sustainable Development Goals).